Implementasi Media Teka - Teki Silang dalam Meningkatkan Minat Belajar Peserta Didik Pada Mata Pelajaran Pancasila Kelas IV Di SD No 2 Sedang Abiansemal Badung - Ni Kadek Puspita Dewi; I Made Arsa Wiguna; I Made Sukariawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning interest is a crucial factor influencing student success in the learning process. However, in the Pancasila subject, fourth-grade students at SD No. 2 Sedang Abiansemal, Badung, still show low levels of student interest, demonstrated by a lack of attention, participation, and enthusiasm. This study aims to analyze the factors contributing to low student interest, describe the application of crossword puzzles to enhance learning interest, and analyze the implications of crossword puzzles for the Pancasila subject. This study used a qualitative descriptive approach grounded in Constructivist Theory and Learning Interest Theory. The subjects consisted of teachers and fourth-grade students. Data collection techniques included observation, structured interviews, and documentation studies. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that low student interest in learning is influenced by internal and external factors. The application of crossword puzzles actively engages students in the learning process. The use of this media has positive implications for increasing student attention, participation, enthusiasm, and interest in Pancasila. Keywords: Crossword Puzzles, Learning Interest, Pancasila Education